CORPORATE SOCIAL RESPONSIBILITY (CSR) ANTARA ETHICS-PERILAKU ORGANISASI-RESPONSIBILITY DAN PENERAPANNYA DI ORGANISASI PEMERINTAH - Rahayu, Amy S. (Direktorat Jenderal Peraturan Perundang-undang, Kementerian Hukum dan Hak Asasi Manusia, 2009)
In recent years the concept of corporate social responsibility(CSR) has gained unprecendented momentum in Europe andUS. A wealth of literature has been published on CSR over thelast 30 years, many containing their own definition of CSRand related concepts. Despite the variety of definitions,probably the most widely accepted and referred toconceptualisation of CSR found in the business andmanagement literature. Archie Carroll, who sees CSR as aconstruct relating to four different areas of business-societyrelation: economic responsibility, legal responsibility, ethicalresponsibility, and philanthropic responsibility.Crowter and Aras, give the reasons of difficult to define CSRis because of the uncertainty surrounding the nature of CSRactivity. He take the view there are three basic principles whichtogether comprise all CSR activity, these are: sustainability,accountability, and transparency. Moreover ethics is alsoinevitably part of business responsibility. Corporate behaviorshould be ethical and responsible, that is why corporatepromise for their shareholders and stakeholders have tobehave fair, ethical, and equitable.The public services is social philanthropic organization, andalmost of them show a organization how to behave properlyin their all operation, but ethics is the problematic area ofpublic services, there is no absolute agreement to whatconstitutes ethical or unethical behaviour, see corruption,gravitation, and so on. Public services organization must bemore than a legal and ethical person, CSR not always a legalnecessity, but increasingly it is obligation.